Clinical case studies in home health care (Wiley-Blackwell, 2011)
Home health care is an important aspect of community health and a growing area of healthcare services. Clinical Case Studies in Home Health Care uses a case-based approach to provide home health care professionals, educators, and students with a useful tool for thoughtful, holistic care.The book begins with a thorough and accessible introduction to the principles of home health care, including a discussion of supporting theoretical frameworks and information on managing complexities, transitioning patients to home care, and preparation for the home visit. Subsequent sections are comprised entirely of case studies organized by body system. Though cases are diverse in content, each is presented in a consistent manner, promoting a logical approach to understanding a patient's presentation, relevant data about the patient and caregivers, and managing patient care. Cases also include helpful tips about reimbursement practices, cultural competence, community resources, and rehabilitation needs.